Uji Efektifitas Beberapa Entomopatogen Pada Larva Oryctes rhinoceros L. (Coleoptera: Scarabaeidae) di Laboratorium - Ridha Hasanah Sihombing; Syahrial Oemry; Lahmuddin Lubis (Universitas Sumatera Utara, 2014)
Research on title The Effectivity of Some Entomopathogenic on the Larvae Oryctes rhinoceros L.(Coleoptera: Scarabaeidae) in the Laboratory